2019-08-21 Περιφερειακό Συμβούλιο - live (Περιφέρεια Δυτικής Μακεδονίας, 2019)
: Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE